2010
DOI: 10.1002/jssc.200900629
|View full text |Cite
|
Sign up to set email alerts
|

RP‐thin layer chromatographic method for the quantification of three gingerol homologs of ultrasonic‐assisted fresh rhizome extracts of Zingiber officinale collected from North Western Himalayas

Abstract: A rapid and sensitive RP high-performance thin-layer chromatographic (RP-HPTLC) methodology was developed and validated for the quantitative estimation of gingerols in methanolic extract of fresh ginger rhizome. The samples were chromatographed on RP-TLC glass plates pre-coated with RP-18 60F(254) as the stationary phase. Linear ascending development was carried out in twin trough glass chamber saturated with ternary-solvent system consisting of acetonitrile-water-formic acid (7:2:1 v/v/v) at room temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…[10] A large number of HPLC and HPTLC methods for the quantification of 6-gingerol in [11,12] ginger oil, [13] crude drugs drink, [14] commercial Ayurvedic formulation [15] and rhizome [16] have been reported in the literature. The literature survey also revealed that quantification of other ginger homologues (8,10 gingerols) with 6-gingerol, [17] other diterpenes in Japanese gingers, [18] green and dried ginger, [19] freeze dried CO 2 extract, [20] three gingerols [21] with 6-shogaol in Jamaican ginger, [22] commercial ginger, fresh and dried rhizome and dietary supplements, [23][24][25] with have also been reported. Until date, no report on chromolithic separation of 6, 8, 10-gingerols and shogaol for the quantification, validation and system suitability in the ginger rhizome has been reported.…”
Section: Hplc Apparatus and Chromatographic Conditionsmentioning
confidence: 92%
“…[10] A large number of HPLC and HPTLC methods for the quantification of 6-gingerol in [11,12] ginger oil, [13] crude drugs drink, [14] commercial Ayurvedic formulation [15] and rhizome [16] have been reported in the literature. The literature survey also revealed that quantification of other ginger homologues (8,10 gingerols) with 6-gingerol, [17] other diterpenes in Japanese gingers, [18] green and dried ginger, [19] freeze dried CO 2 extract, [20] three gingerols [21] with 6-shogaol in Jamaican ginger, [22] commercial ginger, fresh and dried rhizome and dietary supplements, [23][24][25] with have also been reported. Until date, no report on chromolithic separation of 6, 8, 10-gingerols and shogaol for the quantification, validation and system suitability in the ginger rhizome has been reported.…”
Section: Hplc Apparatus and Chromatographic Conditionsmentioning
confidence: 92%
“…HPTLC is a globally accepted rational and practical solution to characterize the crude plant drug, pharmacologically active constituents, enriched standardized extracts and their formulations. In continuation of our study 19, 20, on application of planar chromatography for fingerprinting and chromatographic method development to assure quality of medicinal plants, we report herein a rapid, precise, sensitive and validated high‐performance thin‐layer chromatographic method for triterpenoid's quantitative determination in B. utilis stem bark extracts.…”
Section: Introductionmentioning
confidence: 97%
“…Some high-performance thin layer chromatography (HPTLC) methods have also been reported for the determination of 6-GIN in ginger extract, commercial foods, and commercial formulations [ 20 , 21 , 22 ]. The HPTLC method had also been utilized for the simultaneous determination of 6-GIN, 8-GIN, and 10-GIN in ultrasonication-assisted extract of ginger [ 23 ]. The HPTLC technique was also applied for the determination of a similar compound 8-GIN in plant extracts, commercial foods, and commercial formulations [ 24 ].…”
Section: Introductionmentioning
confidence: 99%